PENGARUH SERTIFIKASI GURU TERHADAP PENINGKATAN KINERJA GURU DI MTs AL-FALAH JONGGRONG MOJOAGUNG KABUPATEN JOMBANG TAHUN PELAJARAN 2014/2015 - Fatoni, - (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
This study is aimed at finding the influence of teachers certification toward the improvement of teachers’ performance at MTs Al Falah Jonggrong Mojoagung. As understood the certification program is the process of granting certificates for professional teachers. The certificate will be obtained through a series of assessments of teachers held by the Institution of Higher Education Teaching appointed by the government. In accordance with the Education Minister Regulation No.18 of 2007, the certification is done by the portfolio. One of the road taken by the government to overcome the low quality of education is to improve the quality of its teachers through teacher certification. The government hopes that, with disertifkasinya teacher, so that its performance will increase student achievement increase. The problem of this study is there any influence of teacher certification to the improved performance of teachers in MTs Al-Falah Jonggrong Mojoagung Jombang in academic year 2014/2015. Data analysis techniques that I use in testing the hypothesis by using independent t test, considering the results of data analysis can be concluded that: There is the influence of teacher certification to the improved performance of teachers in MTs Al-Falah Jonggrong Mojoagung Jombang in academic year 2014/2015. Keywords: Certification, Performance 1 Praktisi